Wintering grounds, population size and evolutionary history of a cryptic passerine species from isotopic and genetic data. (19th September 2020) - de la Hera, Iván; Gómez, Jordi; Dillane, Eileen; Unanue, Azaitz; Pérez‐Rodríguez, Antón; Pérez‐Tris, Javier; Torres‐Sánchez, María
Abstract : Cryptic species pose a particular challenge to biologists in the context of life history investigations because of the difficulty in their field discrimination. Additionally, there is normally a lag in their widespread acceptance by the scientific community once they are formally recognised. These two factors might constrain our ability to properly assess the conservation status of the different species conforming a cryptic complex. In this study, we analysed isotopic and genetic data to shed light into the still unclear wintering grounds, population size and evolutionary history of the Iberian chiffchaff Phylloscopus ibericus, a species included within the common chiffchaff Phylloscopus collybita until two decades ago due to their phenotypic similarity. We used molecular methods to identify spring‐migrating Phylloscopus species captured in northern Iberia, and by comparing the Hydrogen isotopic ratios of their claw tips (δ 2 Hc ; which would reflect the signatures of their wintering grounds), we detected that δ 2 Hc values of Iberian chiffchaffs were similar to willow warblers ( Phylloscopus trochilus ; a renowned trans‐Saharan migrant), and higher than common chiffchaffs (mostly a pre‐Saharan migrant). These results strongly support the idea that Iberian chiffchaffs winter in tropical Africa. We additionally reconstructed the phylogeny and evolutionary history of the Iberian chiffchaff's clade using mitochondrial and nuclear markers. Our results revealed relatively high values of nucleotide diversity (and, hence, high Ne ) for the species that were greater than the values of the common/Iberian most recent common ancestor. This suggests that the Iberian chiffchaff did not experience strong bottlenecks after diverging from the common chiffchaff approximately one million years ago. Ultimately, our study provides another illustrative example of how isotopic and genetic analysis tools can help to enhance our understanding of avian ecology and evolution.